2012
DOI: 10.1007/s10620-012-2299-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Injury Due to Combined Choline-Deprivation and Thioacetamide Administration: An Experimental Approach to Liver Diseases

Abstract: Long-term combined dietary CD and TAA administration could be a more realistic experimental approach to human liver diseases involving severe steatosis, fibrosis, stellate cell activation and significant regenerative hepatocellular response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
1
10
0
2
Order By: Relevance
“…We believe that the increased expression of TIMP‐1 in all studied groups throughout the experiment indicates the activation of the ECM turnover mechanism in the presence of excessive MMP‐9, which is in agreement with previous studies showing that TIMPs arise when the ECM regulation balance has been disturbed . Moreover, in the TAA and the combination group, the moderate gradual increased expression of TIMP‐1 as compared to the respective sharp and intense expression observed in the control and CDD group, could indicate that the augmented/enhanced extracellular matrix degradation under the concomitant TAA and CDD exposure might accelerate the changes of liver architecture, leading to ECM remodelling that inevitably leads to the development of hepatic fibrosis …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We believe that the increased expression of TIMP‐1 in all studied groups throughout the experiment indicates the activation of the ECM turnover mechanism in the presence of excessive MMP‐9, which is in agreement with previous studies showing that TIMPs arise when the ECM regulation balance has been disturbed . Moreover, in the TAA and the combination group, the moderate gradual increased expression of TIMP‐1 as compared to the respective sharp and intense expression observed in the control and CDD group, could indicate that the augmented/enhanced extracellular matrix degradation under the concomitant TAA and CDD exposure might accelerate the changes of liver architecture, leading to ECM remodelling that inevitably leads to the development of hepatic fibrosis …”
Section: Discussionsupporting
confidence: 91%
“…In a previous study of ours, we have demonstrated that concomitant exposure to TAA with CDD over a period of time (30, 60 and 90 days) induces a state of progressive hepatic steatosis and fibrosis along with hepatic stellate cell activation and significant regenerative hepatocellular response with a progressive increase in liver enzymes. This model is compatible with the “two hit” theory in the liver pathology for studying the changes of a prolonged period of time similar to liver‐associated human diseases in clinical practice like chronic liver disease, nonalcoholic steatohepatitis and cirrhosis.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations